1985
DOI: 10.1111/j.1432-1033.1985.tb08955.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of reconstitutively active nicotinamide nucleotide transhydrogenase of Escherichia coli

Abstract: 1. The nicotinamide nucleotide transhydrogenase of Escherichia coli has been purified from cytoplasmic membranes by pre-extraction of the membranes with sodium cholate and Triton X-100, solubilization of the enzyme with sodium deoxycholate in the presence of 1 M potassium chloride, and centrifugation through a 1.1 M sucrose solution. The purified enzyme consists of two subunits, CI and j, of apparent M , 50000 and 47000.2. During transhydrogenation between NADPH and 3-acetylpyridine adenine dinucleotide by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 29 publications
3
30
1
2
Order By: Relevance
“…In contrast to an earlier study [29], (cHxN),C was found to react with both the a and p polypeptides of the enzyme, and we must therefore withdraw an interpretation of our experiments [32], which was based on that finding, that the (cHxN),Creactive group is located within 100 residues of the C-tenninus of the a polypeptide. Furthermore, we can now predict that some or all of the newly identified (cHxN),C label in the p polypeptide, which is enhanced by NADP(H) [39], will be associated with the inhibition of the rate of release of NADP' and NADPH from the enzyme.…”
Section: The Effects Of Nw-dicyclohexylcarbodiimide On the Binding Ocontrasting
confidence: 96%
See 4 more Smart Citations
“…In contrast to an earlier study [29], (cHxN),C was found to react with both the a and p polypeptides of the enzyme, and we must therefore withdraw an interpretation of our experiments [32], which was based on that finding, that the (cHxN),Creactive group is located within 100 residues of the C-tenninus of the a polypeptide. Furthermore, we can now predict that some or all of the newly identified (cHxN),C label in the p polypeptide, which is enhanced by NADP(H) [39], will be associated with the inhibition of the rate of release of NADP' and NADPH from the enzyme.…”
Section: The Effects Of Nw-dicyclohexylcarbodiimide On the Binding Ocontrasting
confidence: 96%
“…The presence of either NADP' or NADPH during treatment increased the degree of inhibition [29]. We confirmed these observations (data not shown).…”
Section: Inhibition By N"-dicyclohexylcarbodiimidesupporting
confidence: 84%
See 3 more Smart Citations